TANGGUNG JAWAB DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL DALAM MENERBITKAN AKTA KELAHIRAN MENGGUNAKAN SATU KATA DI KABUPATEN SEKADAU - NIM. A1011191039, NURUL AGUSTINE (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract This study analyzes the issuance of birth certificates bearing single-word names in Sekadau Regency, notwithstanding Article 5 Paragraph (3) of Minister of Home Affairs Regulation No. 73 of 2022, which stipulates that a name must consist of at least two words. The persistence of this practice is rooted in local traditions and beliefs that long names may become a burden for children or even cause illness, prompting parents to adopt single-word names instead. The research employs an empirical descriptive approach, with data obtained through interviews and questionnaires involving the Civil Registry Office (Disdukcapil) and parents during the period 2022